Monocyte Chemoattractant Protein-1/CCL2 Produced by Stromal Cells Promotes Lung Metastasis of 4T1 Murine Breast Cancer Cells - Yoshimura, Teizo (Public Library of Science, 2013)
MCP-1/CCL2 plays an important role in the initiation and progression of cancer. Since tumor cells produce MCP-1, they are considered to be the main source of this chemokine. Here, we examined whether MCP-1 produced by non-tumor cells affects the growth and lung metastasis of 4T1 breast cancer cells by transplanting them into the mammary pad of WT or MCP-1(−/−) mice. Primary tumors at the injected site grew similarly in both mice; however, lung metastases were markedly reduced in MCP-1(−/−) mice, with significantly longer mouse survival. High levels of MCP-1 mRNA were detected in tumors growing in WT, but not MCP-1(−/−) mice. Serum MCP-1 levels were increased in tumor-bearing WT, but not MCP-1(−/−) mice. Transplantation of MCP-1(−/−) bone marrow cells into WT mice did not alter the incidence of lung metastasis, whereas transplantation of WT bone marrow cells into MCP-1(−/−) mice increased lung metastasis. The primary tumors of MCP-1(−/−) mice consistently developed necrosis earlier than those of WT mice and showed decreased infiltration by macrophages and reduced angiogenesis. Interestingly, 4T1 cells that metastasized to the lung constitutively expressed elevated levels of MCP-1, and intravenous injection of 4T1 cells producing a high level of MCP-1 resulted in increased tumor foci in the lung of WT and MCP-1(−/−) mice. Thus, stromal cell-derived MCP-1 in the primary tumors promotes lung metastasis of 4T1 cells, but tumor cell-derived MCP-1 can also contribute once tumor cells enter the circulation. A greater understanding of the source and role of this chemokine may lead to novel strategies for cancer treatment.